THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND READING COMPREHENSION - Salvator Jelamu; Ida Bagus Nyoman Mantra; Anak Agung Istri Yudhi Pramawati (Academic Journal on English Studies (AJOES), 2022)
This study aimed to determine the relationship between vocabulary mastery and reading comprehension. The sample in this study was eighth-grade students in a junior high school in Bali, consisting of 42 students who were selected using a random sampling method with a lottery system. The researcher used two tests to obtain data on vocabulary mastery and reading comprehensions, such as a vocabulary assessment test for vocabulary mastery and a short answer test for reading comprehension. The data obtained were assessed using the Product Moment formula and analysed using SPSS 26 for windows. Based on data analysis, it shows that there is a high, significant and positive relationship between vocabulary mastery and reading comprehension of eighth students in junior high school. Therefore, answering the research question, there is a substantial relationship between vocabulary mastery and reading comprehension.